A kind of oxygen vacancy rich BiVO4 / NH2-MIL-125 (Ti) photocatalytic material and its preparation method and application

By introducing oxygen vacancy defects on the surface of the photocatalytic material BiVO4/NH2-MIL-125(Ti) and building a heterostructure, the problem of low phenol degradation efficiency of existing photocatalytic materials is solved, and efficient phenol wastewater treatment is achieved.

CN119056496BActive Publication Date: 2025-03-04SHANDONG PETROCHEMICAL INST
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411561653.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-04
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The existing photocatalytic materials are inefficient when degrading phenol wastewater, mainly due to the poor light absorption capacity and the easy recombination of photogenerated carriers.

Method used

Hydrothermal method combined with chemical reduction method was used to prepare oxygen-rich vacancies BiVO4/NH2-MIL-125(Ti) composite photocatalytic materials, and photocatalytic performance was improved by introducing oxygen vacancies defects on the surface of the material and building heterostructures.

Benefits of technology

The efficiency of photocatalytic degradation of phenol is significantly improved. The phenol degradation rate of 0.30-OBQMIL can reach a phenol degradation rate of 92.6% under ultraviolet light irradiation, and the material has stable chemical properties and has good prospects for industrial utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119056496B_ABST
    Figure CN119056496B_ABST
Patent Text Reader

Abstract

The present invention proposes an oxygen-vacancy-rich BiVO4 / NH2‑MIL‑125(Ti) photocatalytic material and a preparation method and application thereof, belonging to the technical field of catalytic materials. The method comprises: grinding BiVO4 / NH2‑MIL‑125(Ti) and NaBH4 to achieve uniform mixing; transferring the mixture to a covered porcelain boat, annealing under vacuum conditions, keeping the mixture warm for reaction, cooling to room temperature in air, washing with deionized water and ethanol to remove unreacted NaBH4; drying to obtain an oxygen-vacancy-rich BiVO4 / NH2‑MIL‑125(Ti) photocatalytic material. The catalyst preparation method of the present invention is simple, the conditions are mild, and the catalytic efficiency is high. In the process of photocatalytic reaction, oxygen vacancy defects serve as photogenerated electron capture centers, which can promote the effective separation of photogenerated electrons and holes, reduce the carrier recombination rate, and significantly improve the photocatalytic performance of the photocatalytic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalytic materials, and in particular to an oxygen vacancy-rich BiVO4 / NH2-MIL-125 (Ti) photocatalytic material and a preparation method and application thereof. Background Art

[0002] Phenol is a common organic pollutant in wastewater from chemical industries such as coal, petroleum and pesticides. Due to its toxicity and benzene ring structure, it is difficult to degrade, which makes phenol have the characteristics of long retention and high biological toxicity. Low concentrations of phenol can denature proteins, while high concentrations of phenol can promote protein precipitation, which has the risk of carcinogenicity and mutagenicity. In addition, phenol is highly corrosive to the skin and mucous membranes, and can cause permanent damage in severe cases. Once it comes into contact with the skin and mucous membranes and is inhaled or enters the human body through the mouth, phenol will destroy the structure of the red blood cell surface membrane protein, causing the cells to lose activity and dissolve, and will cause damage to nerve cells and liver and kidney functions, and in severe cases, it can lead to death.

[0003] The traditional phenol wastewater treatment methods currently used in industry include physical, biological and chemical methods. The physical method uses physical techniques such as adsorption and filtration to extract and separate phenol pollutants from wastewater; the physical method is more commonly used, but it has significant defects such as only transferring phenol pollutants and failing to degrade phenol. The biological method uses microorganisms in the natural environment to biologically oxidize and decompose phenol pollutants in wastewater, converting them into safe, stable and harmless substances; but the biological method is slow and has a low treatment volume. The chemical method uses chemical substances to react with phenol pollutants in water to convert them into harmless or low-toxic substances; but the chemical method requires the consumption of chemical substances, which is costly and prone to secondary pollution.

[0004] Photocatalytic technology is a new type of physical and chemical process that can directly utilize light energy to efficiently degrade phenol pollutants under the action of catalysts. Its reaction conditions are mild, its applicability is wide, and its operation is simple. It is a phenol pollutant treatment process with good application potential. However, most photocatalytic materials currently have disadvantages such as poor light absorption capacity and easy recombination of photogenerated carriers, which leads to low efficiency of photocatalytic decomposition of phenol. This patent uses a hydrothermal method combined with a chemical reduction method to prepare an oxygen-vacancy-rich BiVO4 / NH2-MIL-125 (Ti) composite photocatalytic material for photocatalytic purification of phenol-containing wastewater. NH2-MIL-125(Ti) in the composite catalytic material has a large specific surface area and a highly ordered pore structure. The heterostructure formed by its contact with BiVO4 can form a built-in electric field, drive the directional movement of photogenerated charges, and reduce the carrier recombination rate. The oxygen vacancy defects introduced on the surface of the composite photocatalytic material can serve as electron capture centers, promote the separation of photogenerated electrons and photogenerated charges during the photocatalytic reaction, and further reduce the carrier recombination rate. The two can work together to effectively improve the efficiency of photocatalytic degradation of phenol, and are expected to achieve efficient purification of phenol wastewater. Summary of the invention

[0005] The purpose of the present invention is to propose an oxygen vacancy-rich BiVO4 / NH2-MIL-125 (Ti) photocatalytic material and its preparation method and application. During the photocatalytic reaction, oxygen vacancy defects serve as photogenerated electron capture centers, which can promote the effective separation of photogenerated electrons and holes, reduce the carrier recombination rate, and significantly improve the photocatalytic performance of the photocatalytic material.

[0006] The technical solution of the present invention is achieved in this way:

[0007] The present invention provides a method for preparing an oxygen vacancy-rich BiVO4 / NH2-MIL-125 (Ti) photocatalytic material, which is characterized by comprising the following steps:

[0008] (1) Grinding BiVO4 / NH2-MIL-125(Ti) and NaBH4 to achieve uniform mixing, adding into water, adding dopamine hydrochloride and a catalyst, heating and stirring to react, filtering, washing, and drying to obtain a mixture;

[0009] (2) The mixture was transferred to a covered porcelain boat, annealed under vacuum conditions, kept warm for reaction, cooled to room temperature in air, and then washed with deionized water and ethanol to remove unreacted NaBH4;

[0010] (3) Drying to obtain oxygen vacancy-rich BiVO4 / NH2-MIL-125(Ti) photocatalytic material.

[0011] As a further improvement of the present invention, the mass ratio of BiVO4 / NH2-MIL-125(Ti) to NaBH4 in step (1) is 1.5-2.5:1.

[0012] As a further improvement of the present invention, the annealing temperature in step (2) is 300-400° C., and the insulation reaction time is 0.5-1.5 h.

[0013] As a further improvement of the present invention, the preparation method of BiVO4 / NH2-MIL-125(Ti) is as follows:

[0014] S1. Dissolve NH4VO3 in NaOH solution, dissolve Bi(NO3)3·5H2O in the mixed solution, slowly drop the NH4VO3 solution into the Bi(NO3)3 solution, and adjust the pH value of the system with acetic acid after the addition;

[0015] S2. Weigh NH2-MIL-125 (Ti) and add it to the mixed solution. After continuous stirring, transfer the suspension to a polytetrafluoroethylene reaction liner, place it in a drying oven, and heat the reaction;

[0016] S3. After the reaction is completed, the mixture is cooled to room temperature, centrifuged, washed with distilled water, and dried to obtain BiVO4 / NH2-MIL-125(Ti).

[0017] As a further improvement of the present invention, the mixed solution is a mixture with a volume ratio of H2O:CH3COOH:C2H5OH=30:10:10.

[0018] As a further improvement of the present invention, the molar ratio of NH4VO3 and Bi(NO3)3·5H2O is 1:1, the pH value is adjusted to 4.5-5.5, the temperature of the heating reaction is 75-85°C, and the time is 0.5-1.5h.

[0019] As a further improvement of the present invention, the preparation method of NH2-MIL-125(Ti) is as follows:

[0020] T1. Weigh 2-aminoterephthalic acid and add it to a mixed solution of DMF and anhydrous methanol, and sonicate until dissolved;

[0021] T2. Add anhydrous methanol and tetrabutyl titanate to the solution in T1;

[0022] T3. After mixing evenly, transfer the sample in T2 to a stainless steel autoclave polytetrafluoroethylene reactor and heat the reaction;

[0023] T4. After the reaction was completed, the solid precipitate was naturally cooled to room temperature, and then washed with DMF and methanol, and dried to obtain NH2-MIL-125(Ti).

[0024] As a further improvement of the present invention, the temperature of the heating reaction is 145-155° C. and the time is 40-54 hours.

[0025] The present invention further protects an oxygen-vacancy-rich BiVO4 / NH2-MIL-125 (Ti) photocatalytic material prepared by the above-mentioned preparation method.

[0026] The present invention further protects an application of the above oxygen vacancy-rich BiVO4 / NH2-MIL-125 (Ti) photocatalytic material in phenol degradation reaction.

[0027] The present invention has the following beneficial effects:

[0028] (1) The semiconductor material BiVO4 was loaded on the surface of the MOFs material NH2-MIL-125(Ti) with a large specific surface area and highly ordered pore structure to construct a BiVO4 / NH2-MIL-125(Ti) heterostructure. The chemical reduction method was further used to introduce oxygen vacancy defects on the material surface. Finally, a new oxygen vacancy-rich BiVO4 / NH2-MIL-125(Ti) photocatalytic material was prepared for the purification of phenol wastewater.

[0029] (2) The heterogeneous structure formed by the contact between NH2-MIL-125(Ti) and BiVO4 in the composite catalytic material can form a built-in electric field, driving the directional movement of photogenerated charges and reducing the carrier recombination rate; the oxygen vacancy defects introduced on the surface of the composite photocatalytic material can serve as electron capture centers, promoting the separation of photogenerated electrons and photogenerated charges during the photocatalytic reaction, further reducing the carrier recombination rate; the two can synergistically effectively improve the efficiency of photocatalytic degradation of phenol, and are expected to achieve efficient purification of phenol wastewater;

[0030] (3) This patent uses SEM, UV-Vis and ESR characterization methods to confirm that the prepared new oxygen vacancy-rich BiVO4 / NH2-MIL-125 (Ti) composite photocatalytic material has a regular morphology and structure, good light absorption ability, and a large number of oxygen vacancy defect sites distributed on the surface, and has good photocatalytic degradation performance for phenol. Under ultraviolet light irradiation, 0.30-OBQMIL treats a 50 mg / L phenol solution, and the phenol degradation rate can reach 92.6% after 90 minutes;

[0031] (4) This patent explores and proposes the reaction mechanism of photocatalytic degradation of phenol through free radical capture experiments. In the process of photocatalytic degradation of phenol by oxygen vacancy-rich BiVO4 / NH2-MIL-125(Ti), ·O2 - is the main active substance, followed by OH and H + And through recycling experiments, it is confirmed that the oxygen vacancy-rich BiVO4 / NH2-MIL-125(Ti) composite photocatalytic material has stable chemical properties and good prospects for industrial utilization. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0033] Figure 1 This is the SEM image of NH2-MIL-125(Ti).

[0034] Figure 2 This is the SEM image of BiVO4.

[0035] Figure 3 SEM image of oxygen vacancy-rich BiVO4 / NH2-MIL-125(Ti) composite material.

[0036] Figure 4 Elemental analysis diagram of oxygen vacancy-rich BiVO4 / NH2-MIL-125(Ti) composite material.

[0037] Figure 5 UV-Vis spectrum of photocatalytic material.

[0038] Figure 6 This is the electron paramagnetic resonance spectrum.

[0039] Figure 7 This is the activity test diagram of photocatalytic degradation of phenol.

[0040] Figure 8 This is a diagram showing the mechanism of photocatalytic degradation of phenol by oxygen vacancy-rich BiVO4 / NH2-MIL-125(Ti).

[0041] Fig. 9 This is the mechanism diagram of photocatalytic degradation of phenol by oxygen vacancy-rich BiVO4 / NH2-MIL-125(Ti).

[0042] Fig.10Stability test of oxygen vacancy-rich BiVO4 / NH2-MIL-125(Ti). DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Preparation Example 1 Preparation of NH2-MIL-125(Ti)

[0045] Here’s how:

[0046] T1. Weigh 2-aminoterephthalic acid and add it to a mixed solution of DMF and anhydrous methanol, and sonicate until dissolved;

[0047] T2. Add anhydrous methanol and tetrabutyl titanate to the solution in T1;

[0048] T3. After mixing evenly, transfer the sample in T2 to a stainless steel autoclave polytetrafluoroethylene reactor, heat to 145°C, and react for 40 hours;

[0049] T4. After the reaction was completed, the solid precipitate was naturally cooled to room temperature, and then washed with DMF and methanol, and dried to obtain NH2-MIL-125(Ti).

[0050] Preparation Example 2 Preparation of NH2-MIL-125(Ti)

[0051] Here’s how:

[0052] T1. Weigh 2-aminoterephthalic acid and add it to a mixed solution of DMF and anhydrous methanol, and sonicate until dissolved;

[0053] T2. Add anhydrous methanol and tetrabutyl titanate to the solution in T1;

[0054] T3. After mixing evenly, transfer the sample in T2 to a stainless steel autoclave polytetrafluoroethylene reactor, heat to 155°C, and react for 54 hours;

[0055] T4. After the reaction was completed, the solid precipitate was naturally cooled to room temperature, and then washed with DMF and methanol, and dried to obtain NH2-MIL-125(Ti).

[0056] Preparation Example 3 Preparation of NH2-MIL-125(Ti)

[0057] Here’s how:

[0058] T1. Weigh 2-aminoterephthalic acid and add it to a mixed solution of DMF and anhydrous methanol, and sonicate until dissolved;

[0059] T2. Add anhydrous methanol and tetrabutyl titanate to the solution in T1;

[0060] T3. After mixing evenly, transfer the sample in T2 to a stainless steel autoclave polytetrafluoroethylene reactor, heat to 150°C, and react for 48 hours;

[0061] T4. After the reaction was completed, the solid precipitate was naturally cooled to room temperature, and then washed with DMF and methanol, and dried to obtain NH2-MIL-125(Ti).

[0062] Preparation Example 4 Preparation of BiVO4 / NH2-MIL-125(Ti)

[0063] Here’s how:

[0064] S1. Dissolve 10mmol NH4VO3 in NaOH solution, dissolve 10mmol Bi(NO3)3·5H2O in the mixed solution, slowly drop the NH4VO3 solution into the Bi(NO3)3 solution, and adjust the pH value of the system to 4.5 with acetic acid after the addition.

[0065] S2. Weigh the NH2-MIL-125 (Ti) prepared in Preparation Example 1 and add it to the mixed solution. After continuous stirring, transfer the suspension to a polytetrafluoroethylene reaction liner, place it in a drying oven, heat it to 75°C, and react for 0.5h.

[0066] The mixed solution is a mixture with a volume ratio of H2O:CH3COOH:C2H5OH=30:10:10;

[0067] S3. After the reaction is completed, the mixture is cooled to room temperature, centrifuged, washed with distilled water, and dried to obtain BiVO4 / NH2-MIL-125(Ti).

[0068] Preparation Example 5 Preparation of BiVO4 / NH2-MIL-125(Ti)

[0069] Here’s how:

[0070] S1. Dissolve 10mmol NH4VO3 in NaOH solution, dissolve 10mmol Bi(NO3)3·5H2O in the mixed solution, slowly add NH4VO3 solution to Bi(NO3)3 solution, and adjust the pH value of the system to 5.5 with acetic acid after the addition.

[0071] S2. Weigh the NH2-MIL-125 (Ti) prepared in Preparation Example 1 and add it to the mixed solution. After continuous stirring, transfer the suspension to a polytetrafluoroethylene reaction liner, place it in a drying oven, heat it to 85°C, and react for 1.5h.

[0072] The mixed solution is a mixture with a volume ratio of H2O:CH3COOH:C2H5OH=30:10:10;

[0073] S3. After the reaction is completed, the mixture is cooled to room temperature, centrifuged, washed with distilled water, and dried to obtain BiVO4 / NH2-MIL-125(Ti).

[0074] Preparation Example 6 Preparation of BiVO4 / NH2-MIL-125(Ti)

[0075] Here’s how:

[0076] S1. Dissolve 10mmol NH4VO3 in NaOH solution, dissolve 10mmol Bi(NO3)3·5H2O in the mixed solution, slowly add NH4VO3 solution to Bi(NO3)3 solution, and adjust the pH value of the system to 5 with acetic acid after the addition.

[0077] S2. Weigh the NH2-MIL-125 (Ti) prepared in Preparation Example 1 and add it to the above mixed solution. After continuous stirring, transfer the suspension to a polytetrafluoroethylene reaction liner, place it in a drying oven, heat it to 80°C, and react for 1 hour.

[0078] The mixed solution is a mixture with a volume ratio of H2O:CH3COOH:C2H5OH=30:10:10;

[0079] S3. After the reaction is completed, the mixture is cooled to room temperature, centrifuged, washed with distilled water, and dried to obtain BiVO4 / NH2-MIL-125(Ti).

[0080] Example 1

[0081] A method for preparing an oxygen vacancy-rich BiVO4 / NH2-MIL-125 (Ti) photocatalytic material, characterized by comprising the following steps:

[0082] (1) Grind 1.5 g of BiVO4 / NH2-MIL-125(Ti) prepared in Preparation Example 4 and 1 g of NaBH4 to achieve uniform mixing, add them into water, add dopamine hydrochloride and a catalyst, heat and stir to react, filter, wash, and dry to obtain a mixture;

[0083] (2) Transfer the mixture to a covered porcelain boat, anneal at 300°C for 0.5-1.5 h under vacuum conditions, keep warm for reaction, cool to room temperature in air, and then wash with deionized water and ethanol to remove unreacted NaBH4;

[0084] (3) Drying to obtain oxygen vacancy-rich BiVO4 / NH2-MIL-125(Ti) photocatalytic material.

[0085] Example 2

[0086] A method for preparing an oxygen vacancy-rich BiVO4 / NH2-MIL-125 (Ti) photocatalytic material, characterized by comprising the following steps:

[0087] (1) Grind 2.5 g of BiVO4 / NH2-MIL-125(Ti) prepared in Preparation Example 4 and 1 g of NaBH4 to achieve uniform mixing, add them into water, add dopamine hydrochloride and a catalyst, heat and stir to react, filter, wash, and dry to obtain a mixture;

[0088] (2) The mixture was transferred to a covered porcelain boat, annealed at 400 °C for 1.5 h under vacuum conditions, kept warm for reaction, cooled to room temperature in air, and then washed with deionized water and ethanol to remove unreacted NaBH4;

[0089] (3) Drying to obtain oxygen vacancy-rich BiVO4 / NH2-MIL-125(Ti) photocatalytic material.

[0090] Example 3

[0091] 1. Preparation of NH2-MIL-125(Ti)

[0092] (1) Weigh 2.20 g of 2-aminoterephthalic acid (NH2-BDC), add 36 mL of DMF and 4 mL of anhydrous methanol, mix, and sonicate until dissolved;

[0093] (2) Add 4 mL of anhydrous methanol and 2.4 mL of tetrabutyl titanate to the solution;

[0094] (3) After mixing evenly, transfer the sample in T2 to a 100 mL stainless steel autoclave polytetrafluoroethylene reactor and keep it in a constant temperature drying oven at 150 °C for 48 h;

[0095] (4) After cooling naturally to room temperature, the solid precipitate was washed with DMF and methanol three times each, and dried in vacuo at 80 °C for 12 h to obtain NH2-MIL-125(Ti) yellow solid.

[0096] 2. Preparation of BiVO4 / NH2-MIL-125(Ti)

[0097] (1) Dissolve 2 mmol NH4VO3 in 20 mL 5 mol / L NaOH solution and 2 mmol Bi(NO3)3·5H2O in 50 mL of a mixed solution with a volume ratio of H2O:CH3COOH:C2H5OH=30:10:10. Prepare five groups of solutions on average.

[0098] (2) Slowly add the NH4VO3 solution to the Bi(NO3)3 solution, and after the addition, adjust the pH value of the system to 5 with acetic acid;

[0099] (3) Weigh 0.11 g, 0.14 g, 0.27 g and 0.49 g of NH2-MIL-125(Ti) and add them to four of the mixed solutions respectively, while one of the mixed solutions does not contain NH2-MIL-125(Ti);

[0100] (4) After continuous stirring for 30 min, the suspension was transferred to a polytetrafluoroethylene (100 mL) reaction liner and placed in a drying oven at 80 °C for 3 h.

[0101] (5) After being taken out, the product was cooled to room temperature, centrifuged and washed several times with distilled water, and then transferred to an electric constant temperature drying oven at 80 °C for drying for 12 h to obtain a group of pure BiVO4 and four groups of BiVO4 / NH2-MIL-125(Ti) products with different ratios, namely 0.15-OBQMIL, 0.30-OBQMIL, 0.45-OBQMIL and 0.60-OBQMIL. The numbers in the code refer to the mass fraction of NH2-MIL-125(Ti) in the composite photocatalytic material.

[0102] 3. Preparation of oxygen vacancy-rich BiVO4 / NH2-MIL-125(Ti)

[0103] BiVO4 / NH2-MIL-125(Ti) nanosheets containing oxygen vacancies were prepared by NaBH4 chemical reduction method.

[0104] (1) 0.2 g BiVO4 / NH2-MIL-125(Ti) and 0.1 g NaBH4 were ground to achieve uniform mixing, added to 100 mL water, 1 g dopamine hydrochloride and 0.1 g catalyst were added, heated to 40°C, stirred for reaction for 1 h, filtered, washed, and dried to obtain a mixture;

[0105] The catalyst is a Tris-HCl solution with a pH of 8.5;

[0106] (2) The mixture was transferred to a covered porcelain boat and annealed at 350 °C under vacuum for 1 h. After cooling to room temperature in air, it was washed three times with deionized water and ethanol to remove unreacted NaBH 4;

[0107] (3) Drying at 60°C to obtain BiVO4 / NH2-MIL-125(Ti) containing oxygen vacancies.

[0108] Test Example 1

[0109] The microstructure of the catalyst prepared in Example 1 has an important influence on the performance of the catalyst. The microstructures of pure NH2-MIL-125(Ti), BiVO4 and 0.30-OBQMIL were analyzed by SEM. Figure 1 It can be seen that the microstructure of NH2-MIL-125(Ti) is a polyhedron with a rough and porous surface and an average particle size of 200-300 nm. Figure 2 It can be seen that pure BiVO4 is composed of tightly packed spindle-shaped particles with an average length of about 500 nm. They are stacked and arranged one on another, making the surface of the BiVO4 block rough and having a large number of macroporous structures. Figure 3 It can be seen that the oxygen-rich BiVO4 / NH2-MIL-125(Ti) composite photocatalytic material is in the shape of a micron flower ball, and its surface is rough and porous, indicating that it has a large adsorption capacity and can provide abundant catalytic active sites. In order to further analyze the composite situation of NH2-MIL-125(Ti) and BiVO4 in the oxygen-rich BiVO4 / NH2-MIL-125(Ti) composite photocatalytic material, EDS elemental analysis was performed. Figure 4 It shows that the composite photocatalytic material contains elements such as Bi, V, C, Ti and N. Since Bi and V elements belong to BiVO4, and C, Ti and N elements belong to NH2-MIL-125(Ti), the EDS results show that NH2-MIL-125(Ti) and BiVO4 are well composited and tightly combined. A BiVO4 / NH2-MIL-125(Ti) heterostructure can be formed at the interface where the two have good contact, which is beneficial to the improvement of its photocatalytic activity.

[0110] Test Example 2

[0111] Light absorption capacity is an important indicator for determining the activity of photocatalysts, and UV-Vis DRS is used to characterize the properties of the catalyst. Figure 5It can be seen that the light absorption band edge of pure NH2-MIL-125(Ti) is located at about 470 nm in the visible light region, and it has good light absorption capacity in the ultraviolet light region. BiVO4 also has good light absorption capacity in the ultraviolet light region, and its light absorption band edge is about 530 nm, indicating that BiVO4 can also absorb and utilize part of the visible light. Compared with pure BiVO4 and NH2-MIL-125(Ti), the composite photocatalytic material with oxygen vacancies BiVO4 / NH2-MIL-125(Ti) has a higher light absorption capacity between 200 nm and 800 nm, indicating that oxygen-rich vacancy BiVO4 / NH2-MIL-125(Ti) can absorb both ultraviolet light and visible light, which is beneficial to improve the efficiency of photocatalytic degradation of phenol. The light absorption capacity of the oxygen-rich vacancy BiVO4 / NH2-MIL-125(Ti) composite material is significantly enhanced, mainly because the introduction of surface oxygen vacancies causes the material color to become dark black, which enhances its light absorption effect.

[0112] Test Example 3

[0113] Surface oxygen vacancy defects, as electron capture centers, can significantly improve the separation efficiency of photogenerated carriers. The surface oxygen vacancy concentration of different catalytic materials was characterized and analyzed using ESR. The larger the area of ​​the ESR diffraction peak, the more oxygen vacancy content there is in the sample. Figure 6 As shown, the ESR spectra of BiVO4, NH2-MIL-125(Ti) and 0.30-OBQMIL are shown. The figure shows that the diffraction peak of 0.30-OBQMIL is the most obvious, and is much higher than the diffraction peaks of BiVO4 and NH2-MIL-125(Ti), indicating that there is a high concentration of surface oxygen defects in 0.30-OBQMIL, confirming that the chemical reduction method successfully introduced oxygen vacancies. In the photocatalytic reaction process, oxygen vacancy defects, as photogenerated electron capture centers, can promote the effective separation of photogenerated electrons and holes, reduce the carrier recombination rate, and significantly improve the photocatalytic performance of photocatalytic materials.

[0114] Test Example 4

[0115] The photocatalytic degradation of the samples was simulated at room temperature and under ultraviolet light conditions. The photocatalytic degradation performance of the samples was simulated using ultraviolet light sources.

[0116] (1) Take 0.1 g of catalyst and add 100 mL of phenol solution (50 mg / L) into the water bath circulating jacket beaker of the photocatalytic reactor;

[0117] (2) Start the cooling water circulation, close the instrument door and stir in the dark for 30 min to make the sample evenly dispersed in the solution until the system reaches adsorption-desorption equilibrium;

[0118] (3) After dark adsorption is completed, sample is taken with a syringe (t = 0 min);

[0119] (4) Turn on the light source and maintain magnetic stirring. Turn off the light source every 10 minutes, turn off the magnetic stirrer, remove the beaker, transfer 3-5 mL of the suspension with a syringe, put the beaker back in place, turn on the magnetic stirrer, close the door, and then turn on the light source.

[0120] (5) Use a syringe filter to filter out the solid catalyst in the liquid. Filter each sample 3-5 times to obtain a clear liquid, which is then placed in a sampling tube for later use.

[0121] (6) Use a spectrophotometer to measure the absorbance of the phenol solution sample and calculate the accurate phenol concentration based on the standard curve;

[0122] (7) Continue measuring the phenol concentration until 90 min, record each set of data, and draw a curve.

[0123] In order to further analyze the phenol degradation activity of different photocatalytic materials, a degradation test of 50 mg / L phenol was carried out under ultraviolet light irradiation. The experimental results are as follows: Figure 7 shown.

[0124] Depend on Figure 7 It can be seen that in the absence of a catalyst, the degradation rate of phenol in the solution is low, indicating that the contribution of ultraviolet light alone to the degradation of phenol is small and the photodegradation rate of phenol is low. In addition, the oxygen-vacancy-rich BiVO4 / NH2-MIL-125(Ti) series of composite photocatalysts have a higher overall photocatalytic degradation activity for phenol, which is significantly higher than that of pure NH2-MIL-125(Ti) and BiVO4, indicating that the composite of NH2-MIL-125(Ti) and BiVO4 and the introduction of oxygen vacancies on the surface of the material can improve the photocatalytic degradation activity of phenol. Among the series of oxygen-vacancy-rich BiVO4 / NH2-MIL-125(Ti) composite photocatalysts, 0.30-OBQMIL has the highest photocatalytic degradation activity for phenol, and the phenol degradation rate can reach 92.6% at 90 min. This is mainly because too little or too much NH2-MIL-125(Ti) added to the composite photocatalyst will cause BiVO4 and NH2-MIL-125(Ti) to fail to form an effective heterostructure, that is, the best effect is achieved when the NH2-MIL-125(Ti) addition amount is 30%. In summary, 0.30-OBQMIL is the most efficient photocatalytic material under the experimental conditions.

[0125] Test Example 5 Study on the mechanism of photocatalytic degradation of phenol

[0126] Free radicals OH, H + , and O2 -In order to study the mechanism of photocatalytic degradation of phenol by oxygen vacancy-rich BiVO4 / NH2-MIL-125(Ti), a capture experiment was carried out on 0.30-OBQMIL, and methanol, p-benzoquinone and isopropanol were selected as H + 、O2 - and ·OH capture agent, adding methanol and isopropanol 2 mL, p-benzoquinone 10.8 mg, the degradation curve is as follows Figure 8 The experimental data show that when methanol, p-benzoquinone and isopropanol are added, the degradation of phenol shows different degrees of inhibition, and the inhibition strength is p-benzoquinone>isopropanol>methanol, that is, the degree of influence of free radicals on photocatalytic activity is: ·O2 - > OH>H + , indicating that in the process of photocatalytic degradation of phenol by BiVO4 / NH2-MIL-125(Ti) rich in oxygen vacancies, ·O2 - is the main active substance, followed by OH and H + The main reason may be that the O2 - The amount of O2 generated is relatively large, and - It has a longer lifespan and can fully exert its oxidation effect. Fig. 9 Schematic diagram of the photocatalytic degradation mechanism of phenol. The electrons in the valence band of the oxygen-rich BiVO4 / NH2-MIL-125(Ti) photocatalyst jump to its conduction band under light excitation. The photogenerated electrons can reduce the O2 molecules adsorbed on the surface of the material to produce strong oxidizing O2 - , and further degrade and decompose phenol pollutants; the photogenerated holes left on the valence band of the photocatalyst have strong oxidizing properties and can directly oxidize and degrade phenol pollutants; in addition, the photogenerated holes can also further react with H2O or OH - The reaction generates strong oxidizing ·OH, which is then oxidized to degrade phenol pollutants. In the process of photocatalytic degradation of phenol by oxygen-rich BiVO4 / NH2-MIL-125(Ti), the above three pathways often exist at the same time, and ·O2 - It contributes the most to the degradation of phenol.

[0127] Test Example 6 Study on the stability of photocatalyst

[0128] For the practical application of photocatalysts, one of the most important is the long-term stability and recyclability of the photocatalyst. In order to further explore the stability and recycling ability of the prepared composite photocatalytic material, the photocatalyst was recycled for many times under ultraviolet light and a phenol solution concentration of 50 mg / L, that is, after each photocatalytic degradation experiment, the photocatalyst was recovered and continued to be used after cleaning and drying, and the catalyst was recycled for 5 times. The prepared 0.30-OBQMIL was subjected to a photocatalytic degradation phenol cycle test experiment. Fig.10 The cyclic stability test of the photocatalytic degradation of phenol by 0.30-OBQMIL was performed. Figure 2-8 It can be seen that in the five cycles, there is little change between the cycles, and its phenol degradation efficiency has not decreased significantly, indicating that 0.30-OBQMIL has good photocatalytic stability. The experimental results show that the oxygen-rich BiVO4 / NH2-MIL-125(Ti) has stable chemical properties and has good prospects for industrial utilization.

[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an oxygen vacancy-rich BiVO4 / NH2-MIL-125 (Ti) photocatalytic material, characterized in that: The following steps are involved: (1) Grinding BiVO4 / NH2-MIL-125(Ti) and NaBH4 to achieve uniform mixing, adding them to water, adding dopamine hydrochloride and a catalyst, heating and stirring to react, filtering, washing, and drying to obtain a mixture; the catalyst is a Tris-HCl solution with a pH of 8.5-9.5; (2) The mixture was transferred to a covered porcelain boat, annealed under vacuum conditions, kept warm for reaction, cooled to room temperature in air, and then washed with deionized water and ethanol to remove unreacted NaBH4; (3) drying to obtain oxygen vacancy-rich BiVO4 / NH2-MIL-125(Ti) photocatalytic material; The preparation method of the BiVO4 / NH2-MIL-125(Ti) is as follows: S1. Dissolve NH4VO3 in NaOH solution, dissolve Bi(NO3)3·5H2O in the mixed solution, add the NH4VO3 solution dropwise to the Bi(NO3)3 solution, and adjust the pH value of the system to 4.5, 5 or 5.5 with acetic acid after the addition; S2. Weigh NH2-MIL-125 (Ti) and add it to the mixed solution. After continuous stirring, transfer the suspension to a polytetrafluoroethylene reaction liner, place it in a drying oven, and heat the reaction; S3. After the reaction is completed, cool to room temperature, centrifuge, wash with distilled water, and dry to obtain BiVO4 / NH2-MIL-125(Ti).

2. The preparation method according to claim 1, characterized in that: The mass ratio of BiVO4 / NH2-MIL-125(Ti) to NaBH4 is 1.5-2.5:

1.

3. The preparation method according to claim 1, characterized in that: The annealing temperature is 300-400° C., and the insulation reaction time is 0.5-1.5 h.

4. The preparation method according to claim 1, characterized in that: The mixed solution is a mixture with a volume ratio of H2O:CH3COOH:C2H5OH=30:10:

10.

5. The preparation method according to claim 1, characterized in that: The molar ratio of NH4VO3 and Bi(NO3)3·5H2O is 1:1, the pH value is adjusted to 4.5-5.5, the temperature of the heating reaction is 75-85°C, and the time is 0.5-1.5h.

6. The preparation method according to claim 1, characterized in that: The preparation method of NH2-MIL-125(Ti) is as follows: T1. Weigh 2-aminoterephthalic acid and add it to a mixed solution of DMF and anhydrous methanol, and sonicate until dissolved; T2. adding anhydrous methanol and tetrabutyl titanate to the solution in T1; T3. After mixing evenly, transfer the sample in T2 to a stainless steel autoclave polytetrafluoroethylene reactor and heat for reaction; T4. After the reaction is completed, the solid precipitate is naturally cooled to room temperature, washed with DMF and methanol, and dried to obtain NH2-MIL-125(Ti).

7. The preparation method according to claim 6, characterized in that: The heating reaction is carried out at a temperature of 145-155° C. and for a time of 40-54 hours.

8. An oxygen vacancy-rich BiVO4 / NH2-MIL-125 (Ti) photocatalytic material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the oxygen vacancy-rich BiVO4 / NH2-MIL-125 (Ti) photocatalytic material as claimed in claim 8 in phenol degradation reaction.

Citation Information

Patent Citations

  • Preparation method of organic metal framework composite photocatalyst BiVO4at-NH2-MIL-125 (Ti)

    CN115283015A

  • Preparation method and application of bismuth vanadate nanosheet composite material

    CN116237037A

  • Preparation method of dopamine modified bimetal organic framework antibacterial composite material

    CN116440268A